Antimicrobial susceptibility among Gram-positive and Gram-negative organisms collected from the Latin American region between 2004 and 2015 as part of the Tigecycline Evaluation and Surveillance Trial - Silvio Vega; Michael J. Dowzicky (BMC, 2017)
Abstract Background The in vitro activity of tigecycline and comparator agents was evaluated against Gram-positive and Gram-negative isolates collected in Latin American centers between 2004 and 2015 as part of the Tigecycline Evaluation and Surveillance Trial (T.E.S.T.) global surveillance study. Methods Minimum inhibitory concentrations (MICs) were determined using the broth microdilution methodology according to the Clinical and Laboratory Standards Institute (CLSI) guidelines. Antimicrobial susceptibility was determined using CLSI breakpoints, except for tigecycline for which the US Food and Drugs Administration breakpoints were used. Results A total of 48.3% (2202/4563) of Staphylococcus aureus isolates were methicillin-resistant S. aureus (MRSA). All MRSA isolates were susceptible to linezolid and vancomycin, and 99.9% (2199/2202) were susceptible to tigecycline. Among Streptococcus pneumoniae isolates, 13.8% (198/1436) were penicillin-resistant; all were susceptible to linezolid and vancomycin, and 98.0% (194/198) were susceptible to tigecycline. Susceptibility was >99.0% for linezolid and tigecycline against Enterococcus faecium and Enterococcus faecalis isolates. A total of 40.8% (235/576) E. faecium and 1.6% (33/2004) E. faecalis isolates were vancomycin-resistant. Among the Enterobacteriaceae, 36.3% (1465/4032) of Klebsiella pneumoniae isolates, 16.4% (67/409) of Klebsiella oxytoca isolates and 25.4% (1246/4912) of Escherichia coli isolates were extended-spectrum β-lactamase (ESBL) producers. Of the ESBL-producing K. pneumoniae and E. coli isolates, susceptibility was highest to tigecycline [93.4% (1369/1465) and 99.8% (1244/1246), respectively] and meropenem [86.9% (1103/1270) and 97.0% (1070/1103), respectively]. A total of 26.7% (966/3613) of Pseudomonas aeruginosa isolates were multidrug-resistant (MDR). Among all P. aeruginosa isolates, susceptibility was highest to amikacin [72.8% (2632/3613)]. A total of 70.3% (1654/2354) of Acinetobacter baumannii isolates were MDR, and susceptibility was highest to minocycline [88.3% (2079/2354) for all isolates, 86.2% (1426/1654) for MDR isolates]. Tigecycline had the lowest MIC90 (2 mg/L) among A. baumannii isolates, including MDR isolates. Conclusions This study of isolates from Latin America shows that linezolid, vancomycin and tigecycline continue to be active in vitro against important Gram-positive organisms such as MRSA, and that susceptibility rates to meropenem and tigecycline against members of the Enterobacteriaceae, including ESBL-producers, were high. However, we report that Latin America has high rates of MRSA, MDR A. baumannii and ESBL-producing Enterobacteriaceae which require continued monitoring.